Evidence and policy implications of sanctions in the long run: The case of Iran - Dario Laudati (EconPol Forum, 2023)
Periods of prolonged sanctions can lead to large cumulated economic losses. Oil revenue falls, exchange rate depreciations, and inflation may be key pass-through mechanisms to explain lower output growth. Direct and indirect effects of sanctions may become entrenched over time, leading to resource misallocation. Exclusion from foreign markets pushed Iran to develop in-house innovations and domestic product substitutes. Sanctions may lead to additional socio-economic effects, such as gender-biased policies and reduction of education resources.
Keywords: 330